Estrategias para incorporar redes sociales en los procesos de la cadena de valor del modelo de negocio atención hospitalaria. Caso de estudio: Hospital de los Valles - Caicedo Orbe, María Victoria (2014)
Nowadays, the rapid growth and evolution of Information Technology and Communication have become a support for change as well as energize the current and traditional models of health care in both public and private sectors worldwide. The new way of communication focuses on a new methodology for relationship of humanity, based on digital convergence and translated into the concept of application and use of Social Media. In the case of the “Hospital de los Valles”, as health care facility that provides health services for patients and their families. It has conducted a research study for the diagnosis of the current situation in the management processes of the value chain. As a result, it showed that the processes that should be improved is the admissions process of emergency and external consultation...